Problematika Wewenang Pengawasan Perbankan Dari Bank Indonesia Ke Otoritas Jasa Keuangan - Agus Humaidi (Jurnal Penelitian Hukum Legalitas, 2016)
Bank of Indonesia, the central bank in the national banking system, has authority in the field of banking regulation and supervision. However, Article 34 of Law Number 3 Year 2004 on Amendment to Law Number 23 of 1999 concerning Bank Indonesia mandates the task of supervising banks will be conducted by the institutions supervision of an independent financial services sector, and established by law no later than December 31, 2010. how the effectiveness of the role of the Financial Services Authority in terms of banking supervision is related to Law Number 21 of 2011 on the Financial Services Authority.